Liberal Nationalism and Cosmopolitan Justice - Tan, Kok-Chor (Ethical theory and moral practice, 2002)
Many liberals have argued that a cosmopolitan perspective on global justice follows from the basic liberal principles of justice. Yet, increasingly, it is also said that intrinsic to liberalism is a doctrine of nationalism. This raises a potential problem for the liberal defense of cosmopolitan justice as it is commonly believed that nationalism and cosmopolitanism are conflicting ideals. If this is correct, there appears to be a serious tension within liberal philosophy itself, between its cosmopolitan aspiration on the one hand, and its nationalist agenda on the other. I argue, however, that this alleged conflict between liberal nationalism and cosmopolitan liberalism disappears once we get clear on the scope and goals of cosmopolitan justice and the parameters of liberal nationalism. Liberal nationalism and cosmopolitan global justice, properly understood, are mutually compatible ideals.